Sex differences in the association between lipids and cognitive function in older adults - Jiahao Chen; Yinming Wang; Wenyan Guo; Muyuan Jiang; Zixuan Gai; Huinan Zhang; Mulei Chen; Yifan Fan (All Life)
Background: It is well known that cognitive function is associated with gender differences. However, the effect of sex differences on the relationship between lipids fractions and cognitive function in older adults has been contentious. Methods: 2,170 participants from the U.S. National Health and Nutrition Examination Surveys (1999-2002 and 2011-2014) were included. Total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) were measured. Cognitive function was assessed using the Digit Symbol Substitution Test (DSST). Multiple linear regression models and restricted cubic spline curve fitting were used. Results: Overall, low HDL-C levels were negatively associated with DSST scores in every group. The levels of TC, TG, and LDL-C were not significantly associated with DSST scores, not only in the total population but also in the males. In the females, after adjustment for potential confounding factors, high TC levels were negatively related to DSST scores (OR = −3.590, 95% CI: – 6.343 to – 0.837), and high TG levels were found positively associated with DSST scores (OR = 2.323, 95% CI: 0.159–4.488). Conclusion: Low plasma HDL is associated with cognitive dysfunction in older adults. In older women, high TC levels are positively associated with cognitive decline while high TG levels may protect cognitive function.